Industrialisation and Employment Dynamics in Nigeria: A Sociological Analysis of Job Creation and Labour Market Trends - Imowo Udobia (INTERNATIONAL JOURNAL OF PUBLIC RELATIONS AND SOCIAL SCIENCES, 2026)
Industrialisation has long been positioned as a vehicle for poverty reduction, job creation, and enhanced global competitiveness through trade. This study assessed how industrialisation such as disaggregated into manufacturing, quarrying and mining, and construction, has shaped job creation in Nigeria, with attention to the sociological dimensions of labour-market change. A cross-sectional survey design was adopted, with data collected online, via a researcher-designed questionnaire, from respondents across the country. Descriptive statistics (mean and standard deviation) were used to answer the research questions on 200 valid responses, while regression analysis tested the three study hypotheses at a 95% confidence interval. Results show that manufacturing and quarrying/mining exert a significant positive effect on employment generation, while construction exerts a significant negative effect. Overall, industrialisation is confirmed to significantly influence job creation in Nigeria. The study recommends fostering a macroeconomic environment such as adequate infrastructure, security, and education, that supports manufacturing; encouraging public-private partnerships to draw foreign direct investment into mining and quarrying; and integrating international construction players with domestic firms to expand absorptive capacity in that subsector.